Effects of cinnamaldehyde combined with ultrahigh pressure treatment on the flavor of refrigerated Paralichthys olivaceus fillets. Issue 21 (27th March 2020) - Xu, Yongxia; Yin, Yiming; Zhao, Honglei; Li, Qiuying; Yi, Shumin; Li, Xuepeng; Li, Jianrong
Abstract : The combined effects of cinnamaldehyde (CA) and ultrahigh pressure (UP) treatment on the flavor of olive flounder ( Paralichthys olivaceus ) fillets during storage at 4 °C for 20 days were investigated. Abstract : The combined effects of cinnamaldehyde (CA) and ultrahigh pressure (UP) treatment on the flavor of olive flounder ( Paralichthys olivaceus ) fillets during storage at 4 °C for 20 days were investigated. Changes in total viable count, trimethylamine, ATP-related compounds, free amino acids, TCA-soluble peptides, electronic nose (E-nose) analysis and sensory quality were measured. The results indicated that CA and UP treatment, especially CA combined with UP, significantly reduced undesirable flavor compounds including inosine, hypoxanthine, TMA, and bitter amino acids, and accumulated pleasant flavor compounds such as inosine monophosphate and umami-related amino acids. In addition, the combination of CA and UP was shown to be more effective for retarding protein degradation and microbial growth than CA or UP treatment alone. In accordance with the results of E-nose analysis and sensory evaluation, CA combined with UP treatment had great potential for improving the flavor quality of refrigerated flounder fillets and extending their storage life.